Inovasi Manajemen Keuangan Berbasis Smart Card (SIC) sebagai Mekanisme Behavioral Control dalam Pembentukan Kedisiplinan Santri : Smart Card (SIC)-Based Financial Management Innovation as a Behavioral Control Mechanism in Developing Student Discipline - Bayu Aqil Barroroh; Ahmad Fuad Hasyim HS; Dahlia Dahlia (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the implementation of the Santri Identity Card (SIC) as a digital financial management innovation to enhance student discipline at the API ASRI Tegalrejo Magelang Islamic Boarding School. The research is motivated by the need for Islamic boarding schools to adapt to technological advancements while simultaneously strengthening students’ character development through an orderly, transparent, and accountable financial management system. This study employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The analysis follows the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the SIC has a significant impact on students’ financial behavior. Students become more disciplined, measured, and responsible in managing their pocket money, as all transactions are automatically recorded and can be monitored in real time by administrators and guardians. This level of transparency encourages students to restrain consumptive behavior and to distinguish between needs and wants. For the Islamic boarding school, the SIC enhances administrative efficiency, improves record accuracy, and strengthens institutional financial accountability. However, several challenges remain, including limited digital literacy and occasional technical disruptions. These obstacles can be addressed through continuous training and mentoring. Overall, financial digitization through the SIC not only improves the effectiveness of Islamic boarding school management but also functions as an instrument for fostering Islamic character, particularly discipline and responsibility among students. This innovation demonstrates that technology can be harmoniously integrated into Islamic boarding school education.